Testing the non-linear relationship between environmental policy and economic growth in China - Wang, Zhenhua; Wang, Ning; Li, Rui (Frontiers in Environmental Science, 2025)
IntroductionIn order to achieve the coordinated development of environmental protection and economic growth, China has implemented a series of environmental policies. However, the relationship between environmental policy and economic growth is ambiguous due to regional differences.MethodsIn this study, data of 30 provinces in China from 2010 to 2019 is collected to establish three panel threshold models with three different threshold variables and analyze the relationship between environment policy and economic growth.ResultsThe results of this study are as follows: (1) when the R&D level is less than 9.890, environmental policy is detrimental to economic growth. When the R&D level is between 9.890 and 10.077, environmental policy has a slightly positive impact on economic growth. When the R&D level exceeds 10.077, environmental policy has a significant positive effect on economic growth. (2) When the level of economic development is less than 9.469, environmental policy is detrimental to economic growth. However, when the level of economic development exceeds 9.469, environmental policy has a positive effect on economic growth. (3) When the level of industrial dependence is less than 0.372, environmental policy promotes economic growth. When the level of industrial dependence exceeds 0.372, environmental policy is detrimental to economic growth.DiscussionThe novelty of this study is that there is a proved nonlinear relationship between environmental policy and economic growth, and it is concluded that the influence of environmental policy on economic growth is geographically different. We have made certain suggestions that will help achieve a win-win situation for both environmental protection and economic development.